Editores, libreros y compradores: el estudio del mercado musical en España (1770-1808): Publishers, Booksellers, and Buyers: The Study of the Musical Market in Spain (1770-1808) - Marín, Miguel Ángel (Artigrama, 2022)
Resumen En los últimos años, las narrativas historiográficas han mostrado una visión renovada de la música en la España de la Ilustración: la de un país que, con sus singularidades, supo mostrarse atento a los debates estéticos y las novedades de la cultura musical del momento. Esta perspectiva ha supuesto un viraje sustantivo frente a la idea heredada de un país retrasado, cuando no marginado, con respecto a la vida musical europea. En buena medida, este cambio de perspectiva ha sido posible gracias al estudio de un aspecto crucial como el mercado de la música. Este artículo propone una reflexión sobre las fuentes y la metodología apropiadas para la investigación de este mercado entre 1770 y 1808, en particular, de la red internacional de distribución que tuvo en esos años un extraordinario desarrollo. El análisis crítico que se presenta aquí sobre los agentes implicados, las dinámicas de difusión o el tipo de materiales en circulación, entre otros aspectos, podrá servir de guía para futuros estudios. Un mejor conocimiento del mercado musical permitirá entender las complejas dinámicas de transferencia cultural, en tanto que vinculadas a las fuentes musicales también viajaban prácticas estéticas y sociales asociadas al consumo de la música. Abstract In recent years, historiographical accounts have shown a renewed vision of music in Enlightenment Spain: that of a country that, with its singularities, knew how to be attentive to the aesthetic debates and the novelties of the musical culture of the time. This perspective has meant a substantial departure from the inherited idea of a country that lagged behind, if it was not marginalised, with respect to European musical life. To a large extent, this change of perspective has been possible thanks to the study of a crucial aspect such as that of music market. This article proposes a reflection on the relevant sources and methodology for the investigation of the Spanish music market between 1770 and 1808, in particular, the international distribution network that underwent an extraordinary development in those years. The critical analysis presented here on the agents involved, the dynamics of dissemination and the type of materials in circulation, among other aspects, can serve as a guide for future studies. A better knowledge of the music market will allow us to understand the complex dynamics of cultural transfer, insofar as the aesthetic and social practices associated with music consumption were also linked to musical sources. Keywords Music publishing, Musical market, Network, Published manuscript, Music-sellers, Editors, Buyers